Control System Design for Water Pump Activation in PLC-based Smart Hydroponic Design - Muhammad Edy Hidayat (Universitas Syiah Kuala, 2023)
Food security is one of the issues that is one of the concerns to the country government, and one of the independent efforts made by community on their awareness to meet and achieve food needs on a domestic scale in their respective households is through hydroponic for cultivation of vegetables. Hydroponics works by using water as growing medium instead of soil, however, the use of water as a planting medium requires special treatment thus the plants is able to grow optimally. To ensure that the air content in the water used as a hydroponic growing medium is properly available, a water regulation process is needed. The process of water regulation in the hydroponic system uses regulation of the activation of the water pump motor so that water can be regulated and electrical energy efficiency can still be achieved. This study aims to design and test a PLC-based automation system for the purposes of setting the activation of a water pump in a hydroponic system based on the sunlight conditions in the hydroponic installation being built. By using a light sensor (LDR) to measure the intensity of sunlight in the hydroponic system being built, the activation of the pump motor can be controlled through the use of a PLC device that processes the information obtained from the sensor used. The results of the tests carried out provide information that the designed system has proven effective for use in hydroponic systems with pump water regulation time from 08:00 AM to 04:00 PM.